Adição do óleo de Melaleuca alternifolia na dieta de peixes minimiza efeitos tóxicos causados pelo consumo diário de aflatoxina - Souza, Carine de Freitas (2020)
Mycotoxins are natural toxins produced through the secondary metabolism of toxigenic fungi. More than 400 classes of mycotoxins are found, however, as aflatoxins (AFs), produced mainly by Aspergillus species, including toxigenic and more carcinogens species. When ingested, this mycotoxin causes hepatotoxicity, impairs the antioxidant / pro-oxidant balance and damages biological molecules, including lipids, proteins and DNA. In this sense, a combination of these manifestations leads to oxidative stress and initiates the malfunction of the liver, which is the body's main detoxifying organ. In this context, recent studies have suggested the use of plant extracts, rich in phenolic and flavonoids compounds, which can assist in the absorption of mycotoxins that alleviate their toxic effects in animals. Therefore, the objective of this study was to investigate the antioxidant and anti-inflammatory effects of the essential oil (EO) of the Melaleuca alternifolia - tea tree oil (TTO) is able to abrogates or prevent the damage caused by aflatoxicosis in the hepatic and cerebral tissues, when added to the diet. This work was carried out in three stages: (I) it was investigated as responses of the antioxidant defense system of silver catfish (Rhamdia quelen) against ingestion of AF1 (AFB1), where it was determined that the addition of 1177 μg kg-1 of AFB1 in the practice of oxidative physical activity in the liver. It was observed that intoxication with aflatoxin causes an increase in reactive species to oxygen (ROS) and nitrogen (NOx) and consequent damage to lipids and proteins. In step (II) was evaluated if EO of TTO, added to the fish diet, it would be possible to reduce the toxic effects caused by aflatoxin. In this step, the fish were fed with a concentration of 1mL kg-1 of EO of TTO associated with a diet contaminated with aflatoxin (1177 μg kg-1). It was noted that the addition of EO of TTO to the aflatoxin-contaminated diet showed a protective effect, reduced the increase in ROS levels, and damaged lipids and proteins in the plasma and liver. In step (III), the toxic effects of aflatoxin on the purinergic and cholinergic system in the fish brain were analyzed, in addition to assessing the EO of TTO would be able to reduce the toxic effects caused by aflatoxicosis. It is not known that aflatoxin causes increased activity of acetylcholinesterase (AChE) and adenosine deaminase (ADA). In addition, the expression of the p2y11 receptor was observed, probably in an attempt to deal with an inflammation caused by aflatoxicosis. Taken together, as three stages of the study, corroborate the understanding of the mechanisms of toxicity of aflatoxin and that EO of TTO added in the concentration of 1 mL kg-1 in the diet can be used to increase the antioxidant status and effectively reduce the effects impaired by aflatoxicosis, in addition to reducing the damage in brain tissue associated with aflatoxin.